2017
DOI: 10.1515/biolog-2017-0066
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of the interaction between human holo-transferrin and ciprofloxacin in the presence of silver nanoparticles: spectroscopic approaches

Abstract: The binding of ciprofloxacin (CIP) to human holo-transferrin (HTF) in the presence of silver nanoparticles (AgNPs) has been investigated by fluorescence quenching and circular dichroism (CD) techniques as well as resonance light scattering under physiological conditions. It was determined that the intrinsic fluorescence of HTF was quenched by CIP in the presence of AgNPs through static quenching, thus confirming that a CIP-HTF complex was formed in both the binary and ternary systems. However, the analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…This value is 100-fold larger than the maximum scatter collision quenching constant for quenchers (2.0 × 10 10 M –1 s –1 ) . Therefore, the k q values showed that the quenching mechanism for Hb in the presence of SiO 2 NPs must be due to the complex formation between the proteins and SiO 2 NPs, as reported in static quenching …”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…This value is 100-fold larger than the maximum scatter collision quenching constant for quenchers (2.0 × 10 10 M –1 s –1 ) . Therefore, the k q values showed that the quenching mechanism for Hb in the presence of SiO 2 NPs must be due to the complex formation between the proteins and SiO 2 NPs, as reported in static quenching …”
Section: Resultsmentioning
confidence: 75%
“…30 Therefore, the k q values showed that the quenching mechanism for Hb in the presence of SiO 2 NPs must be due to the complex formation between the proteins and SiO 2 NPs, as reported in static quenching. 31 3.4. Binding Parameters.…”
Section: The Journal Of Physical Chemistry Bmentioning
confidence: 99%
“…Previous studies have investigated ligand binding to serum albumin and have reported it on the order of 10 3 –10 5 M –1 . For the NOS–HSA system, the binding order was also found in a similar range, i.e., 1.77 × 10 4 M –1 , at 298 K. The higher magnitude of the K b value also suggested that, at in vivo conditions, NOS can bind effectively with HSA at the same temperature condition. In addition, from Table , it can be seen that the K b also reduces with increasing temperature due to the instability of the NOS–HSA complex at higher temperatures …”
Section: Resultsmentioning
confidence: 78%
“…8 They suggested that chest pain after sustained strain may be indicative of esophageal perforation. 9,10 Although barium esophagography has up to 10% false-negative results, it is the standard method for diagnosis of esophageal perforation. If oral contrast leaks into the mediastinum, it shows esophageal perforation; otherwise, CT may be better for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…8 They suggested that chest pain after sustained strain may be indicative of esophageal perforation. 9,10…”
Section: Discussionmentioning
confidence: 99%